DIAGNOSIS DINI TOKSOPLASMOSIS KONGENITAL DENGAN PCR CAIRAN AMNION - Umatul Khoiriyah (Jurnal Ilmiah Farmasi, 2005)
ABSTRACTToxoplasmosis is caused by infection with the protozoan Toxoplasma gondii. CongenitalToxoplasmosis is an infection resulting from the transplasental passage of the parasites frominfected mother to the fetus. An acute infection in pregnant women associated with a range ofoutcomes from subclinical infection to intra uterine death.Early diagnosis is important to makedecision, therapy or abortion. At present, prosedur diagnostic of congenital toxoplasmosis usesconventional methode especially serological test,but the conventional methode is time consuming,and has high risk. PCR amniotic fluid is one methode to make dignostic of conegenitaltoxoplasmosis. This is very sensitif and rapid (24 hours) and safer than serological tes of thefetalblood.PCR can be done from 15 week after gestation.Key word: congenital toxoplasmosis- PCR- amniotic fluid.